DNA Origami Seesaws as Comparative Binding Assay. (6th May 2016) - Nickels, Philipp C.; Høiberg, Hans C.; Simmel, Stephanie S.; Holzmeister, Phil; Tinnefeld, Philip; Liedl, Tim
Abstract: The application of commonly used force spectroscopy in biological systems is often limited by the need for an invasive tether connecting the molecules of interest to a bead or cantilever tip. Here we present a DNA origami‐based prototype in a comparative binding assay. It has the advantage of in situ readout without any physical connection to the macroscopic world. The seesaw‐like structure has a lever that is able to move freely relative to its base. Binding partners on each side force the structure into discrete and distinguishable conformations. Model experiments with competing DNA hybridisation reactions yielded a drastic shift towards the conformation with the stronger binding interaction. With reference DNA duplexes of tuneable length on one side, this device can be used to measure ligand interactions in comparative assays. Abstract : Tipping the scale : A balance‐like DNA origami structure is used to study the hybridisation of competing DNA binding pairs. By changing their relative binding energies, the structure is forced into different distinct conformations.